An Exploration of the Dynamic Nature of Psychological Ownership in a Classroom-as-Organization. (September 2021) - Cocieru, Ovidiu C.; Lyle, Matthew C. B.; McDonald, Mark A.
Background: Feelings of ownership play an important role in experiential education and are associated with several positive outcomes. However, researchers have yet to explore the dynamic nature of psychological ownership and its antecedents in experiential courses from the perspectives of the students.Purpose: The authors used the lens of psychological ownership theory to explore the experiences of students in an experiential learning setting.Methodology/Approach: In this study, the authors used repeated waves of semi-structured interviews in a two-semester classroom-as-organization (CAO). They then used a five-step process to identify themes describing the students' experience.Findings/Conclusions: The authors found that different antecedents to psychological ownership worked together at different points in the development of the CAO, that students did not want full control of the CAO (despite their feelings of ownership toward it), and that students anticipated feelings of ownership that persisted after the class had ended.Implications: Educators may struggle to identify the level of control students' need in a CAO to reap the benefits of the experience. Persistent feelings of ownership after experiential learning ends can contribute to student development.